CLIT International : Bulletin de l'ILIS/ILIS Newsletter/Boletin del ILIS. (Genève : ILIS, 1985)
Fonds Suzan Daniel (FSD)
Periodiciteit : ?
Redactie : Centre Femmes, 5 Boulevard Saint-Georges, 1205 Genève
Voortgezet als : ILIS Newsletter
Frans
Periodiek